If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x-3)+5(2-x)=6(1-x)=5x
We move all terms to the left:
4(2x-3)+5(2-x)-(6(1-x))=0
We add all the numbers together, and all the variables
4(2x-3)+5(-1x+2)-(6(-1x+1))=0
We multiply parentheses
8x-5x-(6(-1x+1))-12+10=0
We calculate terms in parentheses: -(6(-1x+1)), so:We add all the numbers together, and all the variables
6(-1x+1)
We multiply parentheses
-6x+6
Back to the equation:
-(-6x+6)
3x-(-6x+6)-2=0
We get rid of parentheses
3x+6x-6-2=0
We add all the numbers together, and all the variables
9x-8=0
We move all terms containing x to the left, all other terms to the right
9x=8
x=8/9
x=8/9
| -22-4z=+10 | | 4x+16+x=64 | | 18x3−8x=0 | | 7=56/m | | 3xx/2=60 | | 9x/11-6=5x/9+4 | | (7x-6)(-8x+1)=0 | | 3x-40=x/2+20 | | 7x+20=5x-9 | | 0=1.5x^2+4x | | Y=7/6x+6 | | 6x-1-(3x-3)=3 | | 2700=6800x | | 8x^2=500 | | 7x+31=10 | | 40÷3q=15 | | 3(x+5)/4+-7(x+3)/10=4 | | 3x/8-3=-5 | | 3*x+x/5-5=1/5+5*x | | 5/8t+14=-1 | | 4q+20=16 | | 12(t+4)-8=88 | | 1/5x+1/3=-1 | | 8c-6=15 | | 2x-8=130 | | x-5/3+4x-9/12=5x-32/9-x+9/21 | | 2(3x+5)=x^2 | | 5t-3=2t+4 | | 186=x-x(.07) | | 2x2-6=3x | | 7x-35=70 | | -6(1-7n=36 |